2021
DOI: 10.3390/birds2040032
|View full text |Cite
|
Sign up to set email alerts
|

Nesting Success and Nesting Height in the Critically Endangered Medium Tree Finch (Camarhynchus pauper)

Abstract: When different introduced species across trophic levels (parasite, predator) invade island systems, they may pose significant threats to nesting birds. In this study, we measure nesting height and infer causes of offspring mortality in the critically endangered Medium Tree Finch (Camarhynchus pauper), an island endemic restricted to Floreana Island on the Galápagos Archipelago. Considering all nests at which a male built a nest, sang and attempted to attract a female (n = 222 nests), only 10.4% of nests produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 84 publications
(98 reference statements)
1
7
0
Order By: Relevance
“…Perhaps older males outcompete younger males for access to preferred habitat. In support of this idea, we have observed male take-overs of nests, and in all cases, older (B5) males supplanted and usurped younger (B0, B1) males from nests they had built (Kleindorfer et al 2021b ). Because older males also have larger badge size (the extent of black plumage on the crown and chin), it is possible that badge size (rather than age per se) predicts the outcome of agonistic interactions, as has been shown in other systems (Olsson 1994 ).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Perhaps older males outcompete younger males for access to preferred habitat. In support of this idea, we have observed male take-overs of nests, and in all cases, older (B5) males supplanted and usurped younger (B0, B1) males from nests they had built (Kleindorfer et al 2021b ). Because older males also have larger badge size (the extent of black plumage on the crown and chin), it is possible that badge size (rather than age per se) predicts the outcome of agonistic interactions, as has been shown in other systems (Olsson 1994 ).…”
Section: Discussionsupporting
confidence: 68%
“…The number of rats and owls has increased across the past decade (Kleindorfer, unpublished data), not least because owls feed on the ever-increasing rat population. Rats are olfactory hunters that are more common predators at nests closer to the ground and owls are visual hunters that are more common predators at nests higher in the canopy (Kleindorfer et al 2021b ). In a previous study, we showed that nests at intermediate heights sustained the most larvae from the introduced Avian Vampire Fly (Kleindorfer et al 2016 ; 2021b ), which is the biggest risk factor for the survival of Darwin’s finches (Kleindorfer and Dudaniec 2016 ; Fessl et al 2018 ; McNew and Clayton 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult flies are nonparasitic but lay their eggs in birds' nests where the hematophagous larvae feed on nestling hosts and brooding mothers (Fessl et al, 2001(Fessl et al, , 2006Fessl & Tebbich, 2002). Several studies have found that the vampire fly can have detrimental effects on the survival of nestling Darwin's finches (Fessl et al, 2010;Kleindorfer et al, 2021;Kleindorfer & Dudaniec, 2016;Knutie et al, 2016;Koop et al, 2011Koop et al, , 2013McNew & Clayton, 2018;O'Connor et al, 2010). However, a recent study found that urban finches on San Cristóbal Island are less affected by and more resistant to the vampire fly than nonurban finches (Knutie et al, 2023), who suffer up to 100% mortality due to the fly (Koop et al, 2013;O'Connor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Philornis downsi has been detected on 15 of the 17 islands across the archipelago, infesting nearly all studied passerine species (Wiedenfeld et al 2007;Fessl et al 2018;McNew and Clayton 2018). Due to its severe mortality effects on hosts, particularly critically endangered Darwin's finch species (Lawson et al 2017;Kleindorfer et al 2021), control and Vol. : (0123456789) eradication of P. downsi on the Galápagos is a high priority.…”
Section: Introductionmentioning
confidence: 99%